Identifikasi Biochar yang Dibuat Dengan Lama Pirolisis yang Berbeda Sebagai Amelioran pada Tanah Gambut - Indrawati, Urai Suci (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2023)
One of the ameliorants that can be used to increase peat soil fertility is biochar. Biochar is a pyrolysis product, derived from burning biomass under conditions of limited or no oxygen. The aim of this experiment was to determine the characteristics of biochar from wood shavings (tatal) and coconut shells, which were heated at 350oC for 3 hours, 4 hours and 5 hours. From the analysis of lignin content, coconut shells are higher (45.20%) than tatal (25.74%), FITR Spectrophotometer results show that coconut shells pyrolyzed for 4 hours have fewer functional groups (8 types of functional groups with 3 aliphatic groups, 3 types aromatic group and 2 inorganic groups), compared to pyrolyzed tiles for 3 hours (9 groups and dominated by aromatic groups (5 types), then aliphatic groups (3 types) and inorganic groups (1 type)). Appearance of surface pores of 4 hour coconut shell biochar, with 1000x magnification, firm and regular in arrangement, macro and micro pore sizes smaller (3,677 µm; 3,688 µm; 5,091 µm) compared to pyrolyzed talc biochar for 3 hours (7,473 µm; 8,901 µm ). Coconut shell biochar has sturdy and neatly arranged pores, it is better as an ameliorant in peat soils compared to talc, because it can store carbon for a longer time. Tart has larger pores and collapses easily, so it rots easily.